2015
DOI: 10.1590/s1679-45082015ao3097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adherence to the guidelines for the management of nausea and vomiting induced by chemotherapy

Abstract: Objective:To assess adherence of the prescribing physicians in a private cancer care center to the American Society of Clinical Oncology guideline for antiemetic prophylaxis, in the first cycle of antineoplastic chemotherapy.Methods:A total of 139 chemotherapy regimens, of 105 patients, were evaluated retrospectively from 2011 to 2013.Results:We observed 78% of non-adherence to the guideline rate. The main disagreements with the directive were the prescription of higher doses of dexamethasone and excessive use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In this study, low rates of adherence to the NCCN guideline were found, similar to what was reported by other authors who assessed agreement with the guidelines for prophylaxis of CINV. [7][8][9][10] In the study by Beauchemin et al, although they included only young patients using antineoplastic agents of moderate and high emetogenic potential, only 36.1% of them received antiemetic therapy according to international guidelines. 7 Nikbakht et al also found a low rate of adherence to the guidelines, especially for the protocols of moderate and high emetogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, low rates of adherence to the NCCN guideline were found, similar to what was reported by other authors who assessed agreement with the guidelines for prophylaxis of CINV. [7][8][9][10] In the study by Beauchemin et al, although they included only young patients using antineoplastic agents of moderate and high emetogenic potential, only 36.1% of them received antiemetic therapy according to international guidelines. 7 Nikbakht et al also found a low rate of adherence to the guidelines, especially for the protocols of moderate and high emetogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…9 Finally, França et al identified low adherence (22%) to the ASCO guideline in the prescriptions of antiemetics of patients exposed to chemotherapy of minimum, low, moderate, and high emetogenic potential in the setting of a Brazilian private hospital and, unlike other authors, found greater adherence in prescriptions containing highly emetogenic chemotherapy. 10 The only PRPh identified in the prescriptions for prophylaxis of acute phase of protocols with high emetogenic potential was the prescription of dexamethasone in underdose (16.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the use of corticosteroids, 5-HT3 receptor antagonists were prescribed for almost 98% of patients being treated for acute and delayed CINV in both the HEC and MEC groups. Overuse of 5-HT3 receptor antagonists may not be specific to China, as this type of non-compliance was documented in a recent study in Brazil (26). Moreover, approximately 20% of patients were treated with more than one 5-HT3 receptor antagonist or corticosteroid, even though this prescribing habit is not recommended by either guideline.…”
Section: Discussionmentioning
confidence: 99%
“…Overuse of 5-HT3 receptor antagonists was documented in a previous study in Brazil. 18 Although continuing ondansetron alone beyond 24 h has a minor role in the control of delayed CINV in patients who received HEC, 19 the benefit has not been as great as that seen with dexamethasone monotherapy. 20 Furthermore, the addition of a 5-HT3 receptor antagonist beyond 24 h along with glucocorticoids did not significantly improve control of delayed emesis as compared with dexamethasone monotherapy.…”
Section: Discussionmentioning
confidence: 99%